Design feedback controller of six pulse three phase rectifier based on differential evolution algorithm - Herlambang Setiadi; Akbar Swandaru; Teguh Aryo Nugroho (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The application of power electronics devices is increasing significantly in this past few year. This condition could happen due to the development of semiconductor technology. The application of power electronics is varied from power plant application to vehicles application. One of the power electronics devices that becoming popular is rectifier. Rectifier can be used to transform AC electricity to DC. This paper presents fully controlled six pulse three phase rectifier which designed to stabilize the DC voltage output on a certain loads variation. PID controller is used as the close loop controller system of the rectifier. To get optimal coordination differential evolution algorithm is used to tune the parameter of PID controller. simulation is carried out in MATLAB/SIMULINK environment. From the simulation results, it is found that the performance of six pulse three phase rectifier can be enhanced significantly by using PID controller based on differential evolution algorithm.